CrowdMap trust management for spatiotemporal data - Lagmay, Janelle M.
Web mapping services allow users to map points-of-interests and share it with others to facilitate collaborative mapping. However, these services lack the ability to attach well-defined values to these data points beyond a generic description field, which severely limits the analytical value of data gathered. Different kinds of spatiotemporal data especially those concerning instances of natural calamlities such like floods, earthquakes, tsunamis, landslides, etc. or even national issues including disease outbreaks, accidents and the like can be mapped and attached with a date/time property. CrowdMap is an open-source platform that extends the basic wed mapping service with querying and validation modules for the maintenance of spatiotemporal data. Mapping occurrences of such events will help in planning on how to solve these problems. When disasters or accidents happen, proper visualization of data can improve how concerned authorities will be respond. The public being the most affected sector are the ones who will benefit most from this mechanism of web mapping. CrowdMap builds on top of web mapping services by adding a temporal dimension and arbitrary attributes to spatial data. These arbitrary attributes varies from one type of spatiotemporal data to another. Data points may be searched, sorted and displayed based on these attributes. Because of its crowd sourced nature, CrowdMap also has a validation layer which identifies erroneous reports and effectively improves the correctness of data.